Migration and movement profiles of a potadromous fish (Brachymystax lenok Pallas 1773) in a highly connected river system (Mongolia). - Kaus, Andrew; Büttner, Olaf; Karthe, Daniel; Schäffer, Michael; Borchardt, Dietrich (PANGAEA, 2018)
The aim of this research was to describe and quantify the seasonal migration patterns and fine-scale movement profiles of Brachymystax lenok, a threatened, potadromous salmonid that inhabits the highly connected, boreal river basins of Siberia and northern Asia. During this study 21 mature individuals were monitored over a 15 month period in the upper Eroo River basin, Mongolia, using passive acoustic telemetry. The time and position of the fish is provided here.
Passive acoustic telemetry data for lenok (Brachymystax lenok Pallas 1773) in the Eroo River and some tributaries (Selenga River basin, Mongolia, 2011-2012)
Keywords: Integrated Water Resources Management in Central Asia: Model Region Mongolia; IWRM-MoMo